Impact of Training on Local Food-Based Supplementary Feeding Knowledge of Posyandu Cadres for Undernutrition Management at Banjar 1 Public Health Center - Christiyanti, Ni Ketut Wenny; Dwijayantari, Si Ayu Dinda; Janendra, Putu Sathiya Adi; Purnami, Kadek Ima (Bali Medical and Wellness Journal, 2025)
Background: Malnutrition remains a significant health challenge in Indonesia, especially among vulnerable groups like young children and pregnant women. Improving the skills and knowledge of posyandu cadres in preparing local food-based supplementary feeding (Pemberian Makanan Tambahan/PMT) can help address this issue effectively. Methods: This study used a quasi-experimental design with a one-group pre-test and post-test approach. A group of posyandu cadres was assessed before and after receiving training on making PMT from local food sources. The Wilcoxon Signed Rank test was used to analyze the significance of knowledge changes. Results: A total of 40 primarily female cadres participated, with age distribution showing 40% aged 36–45 years, 20% aged 26–35 years, 37% aged 46–55 years, and 3% aged 55–66 years. The training on local food-based PMT resulted in a significant increase in knowledge (p <0.001). Conclusion: Training on preparing and processing local food-based PMT effectively increased the knowledge of posyandu cadres. This improvement is essential for better management of malnutrition among toddlers and pregnant women in the Banjar 1 Public Health area.